Giant transverse hysteresis is an asperomagnet - COEY, JOHN MICHAEL DAVID (American Physical Society, 1990)
Comparison of the magnetoresistance of amorphous thin films of Tb80U20 and the nonmagnetic analog Y80U20 reveals hysteresis for the terbium alloy, which extends to fields in excess of 8 T at 4.2 K. Hysteresis is found in the magnetization curve only in fields below 4 T at the same temperature. The magnetoresistance effect, attributed to scattering of electrons by the frozen transverse spin components, which have spatial fluctuations on the scale of the interatomic spacing, is interpreted in terms of the magnetization process of the amorphous alloy. Evidence of weak localization is observed in both films below 1 K.
PUBLISHED
Keywords: Physics